Изменчивость клеточных популяций у сахарной свёклы при различных способах репродукции - Юданова, С.С. (Фактори експериментальної еволюції організмів, 2014)
A goal of the presented paper was to analyze the variability of cell populations in different by origin and breeding methods materials. Methods. The following parameters of stomata guard cell populations were evaluated: average mean of chloroplasts number and plastotipe, variance of the distribution, the integral index D (lnM / lnPt), characterizing cytogenetic tissue fractal and stability of the cell population. Evaluation of significance was carried out Student’s T-test. Results. It was shown that regardless of the method of the reproduction (hybridization or uniparental reproduction) maintains 'pattern' variability corresponding mother plants. Conclusions. Geometric proportion (D), linking the characters of tissue and individual levels indicates instability of cell populations in inbred plants. Besides, both hybridization and uniparental reproduction cell populations were quite stable.